Peran Mahasiswa UIN Sumatera Utara dalam Pemberdayaan Ekonomi UMKM melalui Optimalisasi QRIS sebagai Instrumen Inklusi Keuangan di Desa Pematang Tengah, Kecamatan Tanjung Pura, Kabupaten Langkat - Dewi Fazira; Ikhlasul Amal; M Ikhsani Simanjorang; Laylan Syafina (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2026)
Economic empowerment of rural communities through the strengthening of Micro, Small, and Medium Enterprises (MSMEs) is a crucial pillar in achieving national economic independence. One of the fundamental obstacles faced by MSMEs in rural areas is financial exclusion due to low digital literacy and dependence on conventional cash transaction systems. The Community Service Program (KKN) of students from the State Islamic University of North Sumatra (UIN SU) in Pematang Tengah Village was designed to bridge this gap by optimizing the Indonesian Standard Quick Response Code (QRIS). Through an intensive participatory mentoring approach, students acted as agents of digital transformation who educated, trained, and facilitated 10 local MSME actors in adopting non-cash payment technology. The results of the program show a significant shift from digital skepticism to digital trust. The implementation of QRIS has been proven to increase operational efficiency, financial management accuracy, and strengthen the image of business modernity in the eyes of consumers. This article emphasizes that the role of students is not merely as information deliverers, but as catalysts of social capital that is crucial for the sustainability of digitalization at the village level.